2004
DOI: 10.1099/mic.0.26849-0
|View full text |Cite
|
Sign up to set email alerts
|

Specific growth rate and not cell density controls the general stress response in Escherichia coli

Abstract: In batch cultures of Escherichia coli, the intracellular concentration of the general stress response sigma factor RpoS typically increases during the transition from the exponential to the stationary growth phase. However, because this transition is accompanied by complex physico-chemical and biological changes, which signals predominantly elicit this induction is still the subject of debate. Careful design of the growth environment in chemostat and batch cultures allowed the separate study of individual fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
143
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(156 citation statements)
references
References 50 publications
11
143
2
Order By: Relevance
“…Moreover, because of the production of RpoS (subunit of RNA polymerase, represents a major factor involved in starvation survival), E. coli is able to rapidly adapt to, and tolerate, diverse stress conditions (Lange and Hengge-Aronis, 1991). It was thus shown that high osmolarity (Muffler et al, 1996), extremes and fluctuations of temperature (Muffler et al, 1997), low pH (Bearson et al, 1996) and low growth rate (Ihssen and Egli, 2004) induce rpoS in E. coli cells. Supporting the importance of rpoS, an rpoS À E. coli mutant showed decreased survival (colony-forming unit counts) in stationary phase in seawater (Rozen and Belkin, 2001).…”
Section: E Coli Fate In Natural Habitatsmentioning
confidence: 99%
“…Moreover, because of the production of RpoS (subunit of RNA polymerase, represents a major factor involved in starvation survival), E. coli is able to rapidly adapt to, and tolerate, diverse stress conditions (Lange and Hengge-Aronis, 1991). It was thus shown that high osmolarity (Muffler et al, 1996), extremes and fluctuations of temperature (Muffler et al, 1997), low pH (Bearson et al, 1996) and low growth rate (Ihssen and Egli, 2004) induce rpoS in E. coli cells. Supporting the importance of rpoS, an rpoS À E. coli mutant showed decreased survival (colony-forming unit counts) in stationary phase in seawater (Rozen and Belkin, 2001).…”
Section: E Coli Fate In Natural Habitatsmentioning
confidence: 99%
“…rpoS mutations are common in many selection regimens (Zambrano et al, 1993;Finkel and Kolter, 1999;Notley-McRobb and Ferenci, 2000;Chen et al, 2004;Zinser and Kolter, 2004;Mandel and Silhavy, 2005;Maharjan et al, 2006). In Escherichia coli, as growth rate of the culture declines, the concentration of s 38 within the cell reaches 30% the level of s 70 (Jishage and Ishihama, 1995;Ihssen and Egli, 2004). At this point, s 38 becomes an effective competitor with s 70 for the core RNA polymerase and begins to drive various stress-response genes (Jishage and Ishihama, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic relationships among the strains were measured as the ANI of all pairwise comparisons as described previously (Goris et al, 2007) (Supplementary Table S1). A minimal growth medium as described in the study by Ihssen and Egli (2004) was used for all experiments. Bacterial stock cultures were streaked onto agar plates and incubated overnight.…”
Section: Methodsmentioning
confidence: 99%